THE INFLUENCE OF GRAVITATION ON UNINSPOCTED POSITION OF BODU - Veselin Jovović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Human body acts according to the laws of physics, as well as each thing in the space. The effects of mechanical force on the living thing can be noticed the most obviously within human' s motor and sensory functions. The force of gravity constantly influences human body, with a tendency to pull certain parts of human body towards the earth . Active and passive powers of human organism oppose it, trying to keep the parts of human body within physiologica llimits. The muscles are the only active power in human organism, while bones, joints, and ligaments are the passive power. All powers that maintain normal upright posture should be in balance. Prevailing of the muscular power leads to upright posture and movement, while the prevailing of the forces of gravity leads to immobility, rest and the disturbance of body posture, as well as to the appearance of definite body deformities.